CSDMS Data Components Use Cases - Tian Gan (Hydroshare, 2023)
This collection includes HydroShare resources for the use case Jupyter Notebooks of the CSDMS Data Components (https://csdms.colorado.edu/wiki/DataComponents ). These use cases cover a variety of topics, including landslide susceptibility mapping, modeling of overland flow in a wildfire-impacted catchment, permafrost landscape processes, and wave power. Each use case is designed to demonstrate the application and the capabilities of the CSDMS Data Components. Please click on each HydroShare resource link in this collection to access the corresponding Jupyter Notebook and learn how to run it on the CUAHSI JupyterHub.